2015
DOI: 10.22439/dansoc.v26i4.5035
|View full text |Cite
|
Sign up to set email alerts
|

Voldelig transnational aktivisme: Islamisk Stat, foreign fighters og radikalisering

Abstract: Denne artikel undersøger, hvordan radikaliseringen og mobiliseringen af danske foreign fighters foregår, og hvad der motiverer unge danske muslimer til at drage i krig for en voldelig, revolutionær bevægelse som Islamisk Stat. Den offentlige danske debat om foreign fighters tegner et billede af unge, som via bestemte moskémiljøer, studiekredse i Danmark samt internettet radikaliseres til at tro, at væbnet kamp for kalifatet er en religiøs pligt. I kontrast til dette argumenterer artiklen for, at mange foreign … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
1
1
0
1
Order By: Relevance
“…The Western countries where our data were collected can indeed be perceived as such nations. Our findings further corroborate personal accounts of Western foreign fighters in Syria, who suggested that feelings of alienation and deprivation were among the main drivers behind foreign fighters' decision to travel to Syria and fight for the Islamic State (Lindekilde & Bertelsen, 2015). These analyses, together with our results, illustrate that the context of intergroup relations in host societies is a significant factor in explaining extremism.…”
Section: Discussionsupporting
confidence: 89%
“…The Western countries where our data were collected can indeed be perceived as such nations. Our findings further corroborate personal accounts of Western foreign fighters in Syria, who suggested that feelings of alienation and deprivation were among the main drivers behind foreign fighters' decision to travel to Syria and fight for the Islamic State (Lindekilde & Bertelsen, 2015). These analyses, together with our results, illustrate that the context of intergroup relations in host societies is a significant factor in explaining extremism.…”
Section: Discussionsupporting
confidence: 89%
“…Ikke overraskende viser naervaerende undersøgelse, hvordan Islamisk Stat griber fat om netop de virkemidler, Lindekilde & Bertelsen (2015) også påpeger som de vaesentligste drivkraefter for unges tilslutning til Islamisk Stat. I en undersøgelse af danske fremmedkrigere påpeger Lindekilde & Bertelsen (2015), hvordan personlige udfordringer, følelsen af fremmedgørelse, marginalisering og manglende mening med tilvaerelsen er blandt de primaere årsager hos unge, som har søgt tilslutning til Islamisk Stat. Frem for blot at drage paralleller mellem religiøs ekstremisme og voldelige terrorhandlinger fremhaeves individets søgen efter en stabil identitet som en vaesentlig faktor for Islamisk Stats succes med rekruttering af unge danskere.…”
Section: Islamisk Stats Narrative Repertoireunclassified
“…); one's life is simply less worth living when one feels rejected from a larger social community. The desperation associated with such feelings of meaninglessness and fundamental uncertainty is an often proposed trigger of extremism and radicalisation (Döring ; Hogg : 19–35; Lindekilde & Bertelsen ).…”
Section: Introductionmentioning
confidence: 99%